Avaliação da relação entre insatisfação térmica e produtividade em salas de aula universitárias: uma análise de cluster - Bueno, Ana Maria (2023)
The thermal environment is one of the main factors that influence the thermal comfort and productivity of occupants inside buildings. The relevance of the study of thermal comfort in educational buildings is configured by the fact that a thermally comfortable environment tends to provide better levels of attention and concentration, besides the fact that the poor quality of the indoor environment in classrooms can be a risk to the health and productivity of students. Over the years, research has described the relationship between thermal comfort and productivity, and mathematical models have been established to predict changes in productivity as a function of thermal variations in the environment. In this context this research aimed to evaluate the relationship between thermal dissatisfaction and student productivity in university classrooms through a cluster analysis by hierarchical and non-hierarchical methods (k-means). To determine the actual percentage of dissatisfaction (APD1 and APD2) and productivity (PROD1 and PROD2) two methods were adopted and 4 clusters were obtained. Through the dendrogram it was found that the best solutions, with greater stability are clusters 2, 3 and 4. Through the cluster analysis it was observed the relations between the two productivity methods used, besides other variables, such as thermal dissatisfaction, being PROD2 the most significant variable. It was observed through the post-hoc test that PROD2 in clusters 1 and 2 are statistically equal, with average values of 99.99% and 99.97%, respectively. However, for the same clusters, the selfperceived productivity, PROD1, is statistically different, with mean values of 70.81% and 45.28%, respectively. To confirm the efficiency of the clusters, a discriminant analysis was performed, obtaining a success rate of 95.4%. In comparing the two most populous clusters, the relationship observed was that if self-perceived productivity is the highest, then thermal dissatisfaction based on thermal sensation votes will be the lowest. Furthermore, the results suggest that there is a relationship between time of day and self-perceived productivity. Lower self-perceived productivity was observed in relation to cold sensation, while thermal neutrality is related to higher self-perceived productivity.